Бокситоносность главных тектонических структур земной коры - Сапожников Д. Г. Дмитрий Гаврилович; Богатырев Б. А.; Демина В. Н.; Жуков В. В.; Киселев Л. И.; Никитина А. П.; Чекин С. С. (Москва, Наука, 1988)
Авт. указаны на обороте тит. л.